Mechanical stresses in cellular structures under high hydrostatic pressure - Hartmann, Christoph; Mathmann, Katrin; Delgado, Antonio (Innovative Food Science & Emerging Technologies, 2006)
Mechanical stresses and deformation of cellular structures due to the application of high hydrostatic pressure (HHP) is analysed for two cases. In the first case, a liquid-filled spherical shell with linear elastic material properties is considered as first approximation of a biological cell. The theoretical analysis reveals the existence of severe non-hydrostatic mechanical stresses in the wall of the structure. As second case, a nonlinear model of a yeast cell (Saccharomyces cerevisiae) under high hydrostatic pressure is assessed by use of the finite-element method. It is observed that hydrostatic stress conditions are preserved in the interior part of the cell, while non-hydrostatic stress is encountered in the cell wall. There, von-Mises stress reaches its critical value upon failure (70 ± 4 MPa) at a pressure load between 415 MPa and 460 MPa. This confirms observations of cell wall damage at this pressure as reported earlier by other authors. Industry Relevance of the Content of Manuscript 042405344: The current manuscript considers mechanical stresses included in biological cellular structures when exposed to high hydrostatic pressure. It reveals that current idea about the existence of a hydrostatic stress state in any structure under hydrostatic pressure is incorrect. By use of a linear analytical model and a nonlinear numerical model, it can be shown that heterogeneous mechanical stresses occur in solid bodies as long as latter consist of materials with different mechanical properties. Since this result can be generalised to biological and non-biological macroscopic mechanical structures, the paper is, to some extent, relevant for industrial applications. For example, food packages such as bottles, cans and soft pouches represent such structures consisting of different materials. They might be exposed to heterogeneous mechanical stress leading to damage during high-pressure processing. The authors intend to do research on mechanical stresses in natural and industrial food packages during high-pressure treatment in the future. © 2005 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2006.tech.ITC.stmmec.mechan
Keywords: Cell; High-pressure processing; Mechanical stress; Modelling; Simulation